In vitro Functional Comparison of Different Circulating Progenitor Cell Populations - Lafleche, Jessica (University of Ottawa (Canada), 2010)
Cell therapy has been shown to improve the process of revascularization in ischemic myocardial tissue; however, the search for a cell population that can achieve optimal vasculogenic and/or angiogenic potential is ongoing. This research compared the in vitro functional properties of different circulating progenitor cell (CPC) subpopulations from the peripheral blood and determined whether interactions between subsets of CPCs are involved in mediating their function. Of all populations investigated, a novel population referred to as derived CD133+ cells seemed to exhibit superior functional potential. Furthermore, the migratory ability of the different CPC populations was significantly enhanced in the presence of cytokines/growth factors secreted by cultured monocytes. Lastly, we observed that CPC tubule formation in a pro-angiogenic environment required the support of a mature endothelial cell population. Taken together, these results indicate that specific phenotype and intercellular interactions may be necessary for CPCs to achieve their optimal functional potential for new blood vessel growth.
Keywords: Biology, Molecular.; Biology, Cell.